The Role of Traditional Markets in Improving the Economy of the Community in Indonesia - Cahya, Septyan Budy; Waspodo Tjipto Subroto; Norida Canda Sakti (International Journal of Economics, Commerce, and Management, 2025)
Traditional markets play an important role in the local economy in Indonesia, especially in creating jobs, income distribution, and preserving culture. This study uses a Systematic Literature Review (SLR) approach to analyze literature related to the role of traditional markets in improving the economy of people in Indonesia. Through the analysis of relevant scientific articles, it was found that traditional markets contribute to the informal sector, creating jobs, reducing economic disparities, strengthening social networks, and preserving local traditions and culture. However, challenges such as competition with modern markets and inadequate infrastructure are the main obstacles to the sustainability of traditional markets. This study recommends that revitalizing traditional markets through modernizing facilities, empowering traders, and implementing digital technology should be a policy priority to support inclusive and sustainable local economic development.